ANCANG BANGUN ALAT MONITORING DAN DETEKSI BANJIR SECARA REAL TIME BERBASIS NODEMCU ULTRASONIK HC SR04 MENGGUNAKAN APLIKASI BLYNK - Muqtada , Riqza; Mufarrihah , ftitaahul; Augusta Jannatul Firdaus , Reza (Inovate, 2023)
Flood disasters in villages often occur due to the rainy season and human errors such as throwing garbage in the river etc. Losses occur because residents are not prepared for disasters that will occur. This study uses the Internet of things (IoT) method, namely to connect devices to the internet network using a wifi network. From the research results DESIGN OF REAL TIME MONITORING AND FLOOD DETECTION TOOLS BASED ON NODEMCU ULTRASONIC HC SR04 USING THE BLNYK APPLICATION as follows: 2. When the sensor detects the water level, the buzzer will sound and the LED will light up at each water level. 3. Test results: • SAFE water level from 0-11 • STANDBY water level from 11-21 • DANGER water level from 21-25 4. After that we can see water level data through the Blynk application or on a laptop. From the results of the research and discussion that has been carried out to answer each topic of the problem, it can be concluded that the use of NodeMCU as hardware and the HC-SR04 ultrasonic sensor in combination with the Blynk application can provide a solution for monitoring and detecting floods in real-time. Keywords: River, Internet Of Things (IOT), Blynk, Ultrasonic Sensors.